Analisis Faktor Motivasi, Budaya Lokal, Lingkungan Kerja dan Kualitas Pegawai Berpengaruh terhadap Kinerja Pegawai Kabupaten Keerom Propinsi Papua - Endo, Petrus; Troena, Eka Afnan; Surachman, Surachman; Setiawan, Margono (Jurnal Aplikasi Manajemen, 2011)
The objectives of this research are to: 1) Analyze the motivation factors have an influence on the performance of the government employees; 2) Analyze local cultural factors have an effect on the performance of the government employees; 3) Analyze working environment has influence on the performance of the government employees; 4) Analyze working quality has an impact on government employees performance. The research respondents were government officials working at the government agency and the Office in Keerom, with the total number of 156 employees. The observation was conducted in Keerom. The data analysis method applied was multiple regression. The results of this research show that: 1) Motivation has an significantly influence on the employees performance; 2) Local Cultural significantly affects the employees' performance; 3) Working environment significantly influence the employees' performance; 4) The quality of employees has no significantly effect on employees' performance.